CONTRIBUTING FACTORS OF INTEREST IN THE SELECTION OF SHOPPING MALLS - Ronny H. Walean; Frandy Walean; Yeane Koyongian (Jurnal Ekonomi, 2023)
The study's aim was to pinpoint the variables that went into choosing Manado's shopping centers. Two hundred and ten respondents answered a self-made questionnaire  to determine the factors influencing the choice of shopping mall, a survey and an in-depth interview were both done. The result of the in-depth interviews yielded 31 factors, which were utilized to generate a 29-item questionnaire. Using exploratory factor analysis and primary factor extraction, four factors clustered the 29 items.  Facilities, design and product, location, and channels are four factors that emerge as the contributing factors in choice of shopping centers. Facilities have the highest variance, whereas channels have the lowest variance, which helps to explain the selection of shopping malls. There is no significant relationship between gender and selection of retail centers. The results of the study will aid shopping center owners and retail marketers in understanding why people choose to shop at malls. They can develop their plans for shopping malls based on these pillars